Destination Management in achieving Sustainable Tourism in Bali - Segara, I Komang Bayu (Bali Tourism Board, 2025)
Sustainable Tourism has gained traction and is being developed and implemented in various tourist destinations across Bali. This concept seeks to strike a balance between economic development, cultural preservation, and environmental protection. Local wisdom values such as Tri Hita Karana and Sad Kerthi serve as the philosophical foundation for tourism practices that align with the spiritual, social, and ecological values of Balinese society. this study aims to examine how destination management influences the achievement of sustainability, particularly through the role of regulatory frameworks, stakeholder collaboration, and active community participation. A qualitative descriptive method is employed, with data collection techniques comprising observation through a literature review. this study employs the Destination Management Model (DMM) as the principal analytical framework to explore how destination governance influences the achievement of sustainable tourism. Findings showed Bali is progressively aligning its tourism development with the principles of sustainable destination management. However, significant structural and cultural challenges persist, necessitating multi-stakeholder collaboration, improved governance frameworks, and enhanced community engagement to maintain Bali’s status as a world-class tourism destination without compromising its authenticity. The most pressing challenges include the effectiveness of governance and regulatory enforcement, limited awareness and capabilities among small-scale tourism actors, and the intensifying pressures of unchecked tourism development. To overcome these issues, a holistic approach—grounded in local values and involving active participation from communities, regulators, tourism operators, and tourists themselves—is essential.